Anxiety Level During Covid-19 on the Preparedness of New Normal Adaptation - Cornelia Dede Yoshima Nekada; Thomas Aquino Erjinyuare Amigo; Pauliunus Deny Krisnanto (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2022)
Disaster is a sudden and damaging event, causing both physical and mental harm. From 2019 to the present of 2020, the whole world, including Indonesia, has experienced a pandemic caused by COVID-19. The high number of death victims, the way this disease spreads, social effects for the sufferers and the families, and the unavailability of certain medicines, has caused the anxiety amidst the society. In June 2020, the Indonesian Government socialized the policy for new normal adaptation to the society. This new normal adaptation allows people to conduct their usual activities by maintaining health protocols to prevent the threats of being exposed to COVID-19. However, there are many people who ignore this policy, so this condition worries other people. This study was carried out in an aim to analyze the relationship between people’s anxiety regarding COVID-19 and their preparedness for new normal adaptation. This study analyzed the correlational relationship between the two variables. This study used a cross-sectional quantitative design. The sampling technique in this study was an accidental sampling, with 300 Sleman residents as the sample in the age of 10-70 years who were cooperative and willing to be the respondent of this study. The data in this study were taken directly through google form. The correlation test applied the Spearman Rank. The results of this study show that there is a relationship between the COVID-19 anxiety and the preparedness for new normal adaptation, with p-value = 0,000 and r = - 0.261.